Presence, Face, and Light: The Liturgical Assembly as an Icon - Sauvé, Julien (Studia liturgica, 2022)
Architect Jean-Marie Duthilleul can be reproached with leaving out images in his layout of liturgical spaces. However he may only be tackling the issue in a different way. Indeed the way he fits the assembly in the liturgical space can remind us of the way icons are painted. In this study I will try to see if this hypothesis has any grounding by first recalling the norms concerning liturgical space and images, then by scrutinizing Duthilleul's approach to liturgical space and then by comparing it with that of an iconographer from three specific points of view : presence, face and light.